2017
DOI: 10.2147/copd.s124420
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of umeclidinium/vilanterol for the management of patients with moderate to very severe COPD using an economic model

Abstract: BackgroundBronchodilators such as long-acting muscarinic antagonists (LAMAs) and long-acting β2-agonists (LABAs) are central to the pharmacological management of COPD. Dual bronchodilation with umeclidinium/vilanterol (UMEC/VI; 62.5/25 μg) is a novel LAMA/LABA combination approved for maintenance treatment for patients with COPD.ObjectiveThe objective of this study was to assess the cost-effectiveness of maintenance treatment with UMEC/VI compared with tiotropium (TIO) 18 μg, open dual LAMA + LABA treatment, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…However, additional research is needed to confirm this hypothesis. Consistent with the reduction in COPD-related healthcare costs reported here, several other studies support the economic benefit of UMEC/VI treatment initiation when compared with tiotropium monotherapy [ 25 28 ], open dual LAMA + LABA treatment [ 28 ], or no long-acting bronchodilator treatment [ 28 ]. However, whether a delay in initiation of UMEC/VI has further cost implications in these scenarios remains to be seen.…”
Section: Discussionsupporting
confidence: 86%
“…However, additional research is needed to confirm this hypothesis. Consistent with the reduction in COPD-related healthcare costs reported here, several other studies support the economic benefit of UMEC/VI treatment initiation when compared with tiotropium monotherapy [ 25 28 ], open dual LAMA + LABA treatment [ 28 ], or no long-acting bronchodilator treatment [ 28 ]. However, whether a delay in initiation of UMEC/VI has further cost implications in these scenarios remains to be seen.…”
Section: Discussionsupporting
confidence: 86%
“…This study is the first to compare two LAMA/LABA dual therapies using direct head-to-head data from a randomized, 12-week study [ 24 ], which is the most reliable set of data to include within a cost-effectiveness model [ 24 ]. Other studies have compared LAMA/LABA dual therapy using models with assumptions based on network meta-analyses [ 47 , 48 ], or have used head-to-head data to compare UMEC/VI with TIO monotherapy [ 26 , 49 ]. For example, a UK cost-effectiveness analysis of TIO/OLO found that costs and QALYs associated with TIO/OLO were equal to those of UMEC/VI and IND/GLY.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that umeclidinium/vilanterol treatment would be dominant compared with tiotropium and no long‐acting bronchodilator treatment, and less costly than open‐dual LAMA + LABA treatment in patients with moderate to very severe COPD …”
Section: Clinical Trialsmentioning
confidence: 93%
“…Several studies were reviewed to examine the cost‐effectiveness of umeclidinium/vilanterol (ANORO) compared to both monotherapies and other LABA/LAMA combinations. In one study, umeclidinium/vilanterol (ANORO) treatment for moderate to very severe COPD was associated with lower lifetime medical costs ($82 344) compared with tiotropium ($88 822) open‐dual LAMA + LABA treatment ($114 442), and no long‐acting bronchodilator ($86 751) . Fewer exacerbations were predicted to occur with umeclidinium/vilanterol treatment compared with no long‐acting bronchodilator treatment.…”
Section: Clinical Trialsmentioning
confidence: 99%